DA'WAH MEDIA IN THE SUMBAWA TRIBE: Ethnographic Approach to Lawas Pramuji as Da'wah Media in the Sumbawa Tribe - Maharani, Selma; Rifa'i, Akhmad (Universitas Islam Madura, 2025)
Lawas Pamuji plays a significant role as a da'wah medium. As a respected person in spreading the teachings of Islam and human values in the community. Lawas Pamuji's approach in his da'wah is very inclusive and adaptive to the local culture and traditions of the Sumbawa tribe. This allows it to create a strong resonance between Islamic teachings and the needs and values lived by the people of Sumbawa. The research method used in this study is the ethnographic tradition method, which is a method that involves researchers who are directly involved in the daily lives of the people they research. The results of the research on the role of Lawas Pamuji as a da'wah media in the Sumbawa tribe show that Lawas Pamuji has a significant influence in spreading Islamic religious teachings and human values in the local community. The research also highlights the inclusive and adaptive approach used by Lawas Pamuji in preaching, which allows him to create a strong connection with the people of Sumbawa. The communication methods used by Lawas Pamuji, such as lectures, lectures, sermons, as well as the use of social media and information technology, have proven to be effective in expanding the reach of his da'wah. In addition, social activities carried out such as the development of education and health infrastructure also have a positive impact on improving the quality of life of the community. The implication of this research is the addition and dissemination of information about da'wah and Islamic methodology.